Perbandingan Morfologi Dua Jenis Anggrek Epifit pada Pohon Rambutan ( Nephelium lappaceum L.) : Acriopsis liliifolia (J.Koenig) Seidenf. dan Dendrobium crumenatum Sw. - Nery Sofiyanti (Al-Kauniyah: Jurnal Biologi, 2014)
The stem of rambutan tree (Nephelium lappaceum) has suitable microenvironment for the growth of epiphytic flora, due to its rugose stem. Therefore, it may trap and collect plant debrish or other organic material as well as rain drops. One of plant group found on the rambutan tree is orchid (Orchidaceae). This study aimed to observed the morphology of epihytic orchids on rambutan tree. The result showed two orchid species, Acriopsisliliifolia (J. Koenig) Seidenf. and Dendrobium crumenatum Sw.